CHINA’S DUAL CIRCULATION STRATEGY AND THE RECONFIGURATION OF CHINA–GERMANY MANUFACTURING RELATIONS - Ernawati; Arifin Rivai, Aspin Nur (UIN Alauddin Makassar, 2026)
This article examines how China's Dual Circulation Strategy reshapes China–Germany economic cooperation in the manufacturing sector. Using a qualitative case study of bilateral manufacturing relations after 2020, it analyses how China's state-capitalist industrial strategy affects German manufacturing through changes in trade patterns, investment localization, industrial competition, supply-chain dependence, and state-business relations. The article argues that Dual Circulation should not be read as economic isolation or direct decoupling. It is better understood as a state-led effort to strengthen domestic demand, technological self-reliance, and industrial capacity while preserving external circulation where it supports China's upgrading. For German manufacturers, Dual Circulation produces a more selective and contested form of interdependence. China remains an important market, production base, and supply-chain node, while also becoming a stronger competitor in automobiles, batteries, machinery, chemicals, and advanced industrial technologies.